The study-reflection group as a theoretical-methodological perspective for continuing education: a study with public managers of special education - Almeida, Mariangela Lima; Silva, Rayner Raulino; Alves, Janaina Borges (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2017)
This essay is focused on the debate about continuing education of teachers and education managers that aims to guarantee schooling for students with disabilities, pervasive developmental disorder and high abilities/intellectual giftedness. It approaches the prospective of movements and policies in favor of education inclusion, focusing on researches that studies  public managers of special education’s training and performance. It analyses constitutive elements of a study-reflection group of managers/researchers and researchers/academics whom dedicate themselves to comprehend what is possible in the process of creating policies for continuing education in a inclusive perspective. This study has as theoretical-epistemological referential a critical-collaborative action research and Jürgen Habermas theorization. The group’s courses is taken from presencial and virtual dialogs recorded on field notes, meetings’ records, group meetings’ transcription and promoted seminars. It reflects methodological elements that traces the constitutive path of this group and problematizes the researcher’s place in the continuing education’s knowledge construction. The process experienced enhance the possibility of a critical perspective of continuing education promoted by study-reflection groups.